PENGEMBANGAN ALAT PERAGA SISTEM AUDIO UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PENDIDIKAN TEKNIK OTOMOTIF - Andi Irawan; Dwi Widjanarko (Universitas Negeri Yogyakarta, 2019)
This research aims to know the feasibility and the effectiveness of media equipment installation of car audio system use of props to students in Mechanical engineering Department of Semarang State University. This research is a type of research R D. The subject of this study is a student with a total of 60 people divided into 2 classes namely the control class and the experimental class. The object of this research is the medium of audio system installation props. The results of the media test percentage assessment amounted to 88% and the presentation of the material test amounted to 78%, both obtained very decent criteria. The average increase of experimental class learning results was 77.33, while the control class was only 71.47. T test result for post-test value obtained 3.40. The results of the N-gain test calculation obtained an average gain of 0.298 for the control class with a low increase and 0.404 for the experimental class with a moderate increase. The results proved that the installation equipment Media Car audio system is an effective medium to be used as a learning medium.